Surgical treatment odontogenetic compression injury of inferior alveolar nerve after endodontic treatment (Эндодонтия Today, 2020)
Problem of prevention and treatment of complications arising from the root canal teeth with different materials, remains urgent. The article deals with the surgical treatment of odontogenic compression injury of inferior alveolar nerve after endodontic procedures. Surgery is to remove the filling material of the mandibular canal. Of the 92 examined patients operated on 89 patients, 3 persons refused the surgery. Found that treatment of patients with acute compression-toxic neuropathy inferior alveolar nerve, severe complications should begin as early in intensive care, treating this disease, as the urgency of. The developed method is rapid access to the mandibular canal has advantages over access by gingival margin and horizontal cutting method, with the ability to remove all the filling material, to receive an autograft for closure of the defect cortical bone jaw, prevent gum recession in the post-operative period and gives a positive result in 98% of cases